Social water management: collective organization for the market and community management in the Altos de Morelos, Mexico - Vargas-Velázquez, Sergio (Cooperativismo & Desarrollo, 2024)
The social organization of water for small irrigation or human consumption is built on the collective and cooperative action of the beneficiaries themselves, who create their own rules to manage water, preferably as a resource for common use. They establish criteria for distributive equity and sanction those who do not comply with them. In the north of the state of Morelos, Mexico, in small and medium-sized localities, access to water for productive purposes is achieved through membership in irrigation communities, based on identity principles and local norms for access to water that respond to local autonomy from government entities. However, currently these norms no longer guarantee an equitable distribution of water. The promotion of commercial crops in recent decades, together with the increase in irrigation through low-cost technological innovations, such as ’hoyas’ or water boxes, hoses and low-pressure irrigation systems, has led to the abandonment of subsistence crops, as well as socioeconomic differentiation among small-scale producers and the overexploitation of water resources. The two cases analyzed in the Altos de Morelos exemplify the resistance and hybridization of peasant irrigation.